Selenized Polymer-Lipid Hybrid Nanoparticles for Oral Delivery of Tripterine with Ameliorative Oral Anti-Enteritis Activity and Bioavailability - Yuehong Ren; Chunli Qi; Shuxian Ruan; Guangshang Cao; Zhiguo Ma; Xingwang Zhang (MDPI AG, 2023)
The oral delivery of insoluble and enterotoxic drugs has been largely plagued by gastrointestinal irritation, side effects, and limited bioavailability. Tripterine (Tri) ranks as the hotspot of anti-inflammatory research other than inferior water-solubility and biocompatibility. This study was intended to develop selenized polymer-lipid hybrid nanoparticles loading Tri (Se@Tri-PLNs) for enteritis intervention by improving its cellular uptake and bioavailability. Se@Tri-PLNs were fabricated by a solvent diffusion-in situ reduction technique and characterized by particle size, ζ potential, morphology, and entrapment efficiency (EE). The cytotoxicity, cellular uptake, oral pharmacokinetics, and in vivo anti-inflammatory effect were evaluated. The resultant Se@Tri-PLNs were 123 nm around in particle size, with a PDI of 0.183, ζ potential of −29.70 mV, and EE of 98.95%. Se@Tri-PLNs exhibited retardant drug release and better stability in the digestive fluids compared with the unmodified counterpart (Tri-PLNs). Moreover, Se@Tri-PLNs manifested higher cellular uptake in Caco-2 cells as evidenced by flow cytometry and confocal microscopy. The oral bioavailability of Tri-PLNs and Se@Tri-PLNs was up to 280% and 397% relative to Tri suspensions, respectively. Furthermore, Se@Tri-PLNs demonstrated more potent in vivo anti-enteritis activity, which resulted in a marked resolution of ulcerative colitis. Polymer-lipid hybrid nanoparticles (PLNs) enabled drug supersaturation in the gut and the sustained release of Tri to facilitate absorption, while selenium surface engineering reinforced the formulation performance and in vivo anti-inflammatory efficacy. The present work provides a proof-of-concept for the combined therapy of inflammatory bowel disease (IBD) using phytomedicine and Se in an integrated nanosystem. Selenized PLNs loading anti-inflammatory phytomedicine may be valuable for the treatment of intractable inflammatory diseases.